2023
DOI: 10.1002/erv.3033
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal investigation of patients receiving involuntary treatment for extremely severe anorexia nervosa

Florent Abry,
Philip Gorwood,
Mouna Hanachi
et al.

Abstract: IntroductionInvoluntary treatment may be a life‐saving option for extremely severe anorexia nervosa (AN) in the context of life‐threatening conditions and refusal of care. The long‐term outcomes of patients undergoing involuntary treatment for AN are poorly understood. This study aims to explore quality of life, long‐term outcomes and attitudes towards involuntary treatment in patients involuntarily treated for extremely severe AN.Methods23 patients involuntarily admitted for extremely severe AN (I‐AN), and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, study results for adult as well as adolescent patients with AN all suggested that the overall effect of IVT is comparable to that of voluntary treatment regarding treatment outcomes [8,26,37]. First, similar results on weight gain and BMI at discharge were reported across all studies [8,37,39], with one earlier study from 2000 even reporting greater weight gain for involuntarily admitted patients [50]. These results demonstrate that IVT does not seem to be inferior to voluntary treatment regarding weight gain and that the potentially lower weight at admission is successfully increased.…”
Section: Comparison Of Treatment Outcomes-voluntary Vs Involuntary Ad...mentioning
confidence: 69%
See 2 more Smart Citations
“…However, study results for adult as well as adolescent patients with AN all suggested that the overall effect of IVT is comparable to that of voluntary treatment regarding treatment outcomes [8,26,37]. First, similar results on weight gain and BMI at discharge were reported across all studies [8,37,39], with one earlier study from 2000 even reporting greater weight gain for involuntarily admitted patients [50]. These results demonstrate that IVT does not seem to be inferior to voluntary treatment regarding weight gain and that the potentially lower weight at admission is successfully increased.…”
Section: Comparison Of Treatment Outcomes-voluntary Vs Involuntary Ad...mentioning
confidence: 69%
“…This review article summarized the scarce empirical data comparing voluntary and involuntary treatment in patients with AN with a special focus on children and adolescents, suggesting no specific inferiority of IVT regarding the specific treatment outcomes at different follow-up points [8,26,37,39,50]. However, involuntary hospital treatments have been shown to take longer [8,37], and patients admitted involuntarily seem to struggle significantly more during weight restoration, with a higher rate of nasogastric feeding [8,26], a higher rate of refeeding syndrome [55], and increased use of psychotropic medications [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation